Knowledge and perceptions of preconception care among health workers and women of reproductive age in Mzuzu City, Malawi: a cross-sectional study - Mtondera Munthali; Isabel Kazanga Chiumia; Chrispin Mandiwa; Saul Mwale (Reproductive Health, 2021)
Plain Language summary World health organization defines preconception care as the provision of biomedical, behavioral and social interventions to women and couples before the occurrence of conception. In sub-Saharan Africa, there is poor preconception care practices which has resulted into high infant and maternal mortalities. This study examined the knowledge and perceptions of preconception care among health workers and women of reproductive age in order to provide evidence based outcomes for tailored interventions and policy direction. A semi-structured questionnaire and structured interviews were used to assess the knowledge level and perceptions of preconception care among women of reproductive age and health workers respectively. Of the 253 women, 57.7% showed good level of knowledge of preconception care while 42.3% had poor knowledge. Most (72%) women with good knowledge level lacked awareness that they can talk to a health worker before getting pregnant. Most (74.7%) women showed a positive perception towards preconception care which was strongly linked to having good knowledge based on the academic level attained. Those with secondary and tertiary backgrounds were more likely to have good knowledge than those with primary school level education. The majority (95%) of health workers were unable to explain well about preconception care but they admitted their role in preconception care.